2002
DOI: 10.1039/b111263e
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated fractionation of heavy metals in contaminated soils and sediments using rotating coiled columns

Abstract: A new approach to performing an accelerated sequential extraction of trace elements from solid samples has been proposed. It has been shown that rotating coiled columns (RCC) earlier used in counter-current chromatography can be successfully applied to the dynamic leaching of heavy metals from soils and sediments. A solid sample was retained in the rotating column as the stationary phase under the action of centrifugal forces while different eluents (aqueous solutions of complexing reagents, mineral salts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 25 publications
0
45
0
4
Order By: Relevance
“…(1) When L < 0, particles in the rotating column move against the carrier liquid flow, hence (12) or (13) (2) When L = 0, particles are retained in the flow (14) (3) When L > 0, particles move in the column along the carrier liquid flow (15) It may be supposed that, during the quasistationary motion of a particle in the direction of the carrier liquid flow, the tangential centrifugal force is balanced by the force of resistance to the particle motion; hence, F t ≈ F g . Then, with regard to (4) and (5), we have (16) Thus, the velocity of particle motion along the column wall with respect to the carrier liquid flow (v rel ) is proportional to the squared particle radius.…”
Section: Assessment Of Different Modes Of Particle Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) When L < 0, particles in the rotating column move against the carrier liquid flow, hence (12) or (13) (2) When L = 0, particles are retained in the flow (14) (3) When L > 0, particles move in the column along the carrier liquid flow (15) It may be supposed that, during the quasistationary motion of a particle in the direction of the carrier liquid flow, the tangential centrifugal force is balanced by the force of resistance to the particle motion; hence, F t ≈ F g . Then, with regard to (4) and (5), we have (16) Thus, the velocity of particle motion along the column wall with respect to the carrier liquid flow (v rel ) is proportional to the squared particle radius.…”
Section: Assessment Of Different Modes Of Particle Motionmentioning
confidence: 99%
“…It has been shown that coiled columns are suitable not only for the separation of solutes in liquid-liquid, liquid-solid [13,14], and liquid-solid-liquid systems [15], but also for particle fractionation [16,17]. In the last case, there is no liquid phase at all.…”
mentioning
confidence: 99%
“…A new effective method for the direct recovery of toxic organic substances (polycyclic aromatic hydrocarbons, PAHs) from liquid sewage sludge [134] and soil [135] has been proposed. A new continuous-flow method has been also developed that enables not only the fast and efficient fractionation of TE species in soils and sediments to be achieved but allows time-resolved (kinetic) studies on the mobilization of trace and major elements in different forms to be made [136][137][138]. The method is time-saving and requires only 4-5 h instead of the several days needed for routine sequential extraction (traditionally used for the fractionation of TEs to assess their mobility and potential bioavailability).…”
Section: Other Applications Of Hydrodynamic CCC Columnsmentioning
confidence: 99%
“…The main assets of dynamic fractionation are as follows: (1) accurate monitoring of the ongoing leaching of trace and major elements; (2) simplification of the overall procedure (from days to hours); (3) minimization of risks of sample contamination and straightforward manipulation of leaching agents; and (4) evaluation of the efficiency and selectivity of the extractants as well as the maximum pool of available fractions [9]. Among the dynamic approaches suited for the fractionation of trace elements in environmental substrates, the so-called rotating coiled column (RCC) extraction [10], microcolumn (MC) extraction [11][12][13], and stirred flow cell extraction [14,15] should be mentioned. In RCC, the particulate sample (usually 500 mg) is retained by centrifugal forces, whereas different eluents are continuously pumped through.…”
Section: Introductionmentioning
confidence: 99%